2005
DOI: 10.2174/092986705774462888
|View full text |Cite
|
Sign up to set email alerts
|

Nonpeptide Ligands That Target Peptide-Activated GPCRs In Inflammation

Abstract: The focus of this review is on G protein-coupled receptors (GPCRs) for which nonpeptidic ligands are known and have been evaluated for the treatment of inflammatory conditions. GPCRs are the most prevalent class of cell surface proteins in pharmaceutical research today, and GPCR-targeting drugs account for one tenth of worldwide pharmaceutical sales. Of over 800 human GPCRs identified to date, several hundred are activated by peptides/proteins and just over 30 of these have been identified so far as potential … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2006
2006
2011
2011

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 104 publications
0
19
0
Order By: Relevance
“…However, in the case of the type 2 G-protein-coupled receptors (i.e. receptors for VIP, UCN and AM), the pharmaceutical industry has so far failed to generate effective specific non-peptide agonists [102]. Understanding the structure-function relationship of these neuropeptides and their specific receptors – including receptor signaling, internalization, and homo- and heterodimerization in physiological and pathologic situations – will facilitate the development of novel pharmacological agents.…”
Section: Are Neuropeptides Ready For the Clinic? Advantages Versus Pimentioning
confidence: 99%
“…However, in the case of the type 2 G-protein-coupled receptors (i.e. receptors for VIP, UCN and AM), the pharmaceutical industry has so far failed to generate effective specific non-peptide agonists [102]. Understanding the structure-function relationship of these neuropeptides and their specific receptors – including receptor signaling, internalization, and homo- and heterodimerization in physiological and pathologic situations – will facilitate the development of novel pharmacological agents.…”
Section: Are Neuropeptides Ready For the Clinic? Advantages Versus Pimentioning
confidence: 99%
“…These data have established an important role for miRNA-7 in controlling EGFR mRNA expression and have indicated that miRNA-7 has the ability to coordinately regulate EGFR signaling in multiple human cancer breast cancer cells, particularly in TNBC and glioblastoma [76, 77]. Non-peptide ligands that target peptide-activated GPCRs have been developed for treatment of inflammation and obesity [78, 79]. It is likely that development of antagonists selective for GPCR-30 deserves a great potential as therapeutic targets in TNBC.…”
Section: Gpcr-30/egfr Signaling Pathways and Therapeutic Strategiementioning
confidence: 99%
“…An attractive strategy is the development of nonpeptide receptor agonists. However, in the case of the type 2 GPCRs, including VIP, urocortin, αMSH and adrenomedullin receptors, the pharmaceutical industry has so far failed to generate effective nonpeptide-specific agonists (Blakeney and Fairlie, 2005). Even where synthetic agonists were designed specifically for VIP receptors, they were less effective than the natural peptide in terms of anti-inflammatory activity (Delgado et al, 2004).…”
Section: Are Neuropeptides Ready For the Clinic?mentioning
confidence: 99%